1993
DOI: 10.1021/bi00085a018
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 4A4: Expression in Escherichia coli, purification, and characterization of catalytic properties

Abstract: Rabbit lung prostaglandin omega-hydroxylase (P450 4A4) was expressed in Escherichia coli using the isopropyl beta-D-thiogalactopyranoside (IPTG) inducible expression vector pCWori+, containing the full-length cDNA encoding the P450 4A4. The first seven codons were changed to reflect E. coli codon bias [a modification of the method of Barnes et al. (1991) Proc. Natl. Acad. Sci. U.S.A. 88, 5597-5601]; only the second residue of P450 4A4 was altered (Ser to Ala), while the remaining mutations were silent. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…To induce expression of the recombinant protein, 2 ml of an overnight culture were used to inoculate 100 ml of LB (200 g/ml ampicillin). The cultures were then grown with shaking (250 rpm) at 37°C for 2 h. Thirty minutes before induction with 1 mM isopropyl-1-thio-␤-D-galactopyranoside, a 75 g/liter concentration of the heme precursor 5-aminolevulinic acid was added (27), and the cells were then grown for 20 h at the reduced temperature of 30°C (28). The cells were harvested by centrifugation at 5000 ϫ g for 5 min and washed once with 100 mM Tris-HCl, pH 8, 1 mM phenylmethylsulfonyl fluoride.…”
Section: Methodsmentioning
confidence: 99%
“…To induce expression of the recombinant protein, 2 ml of an overnight culture were used to inoculate 100 ml of LB (200 g/ml ampicillin). The cultures were then grown with shaking (250 rpm) at 37°C for 2 h. Thirty minutes before induction with 1 mM isopropyl-1-thio-␤-D-galactopyranoside, a 75 g/liter concentration of the heme precursor 5-aminolevulinic acid was added (27), and the cells were then grown for 20 h at the reduced temperature of 30°C (28). The cells were harvested by centrifugation at 5000 ϫ g for 5 min and washed once with 100 mM Tris-HCl, pH 8, 1 mM phenylmethylsulfonyl fluoride.…”
Section: Methodsmentioning
confidence: 99%
“…coli cells transformed with this plasmid were grown in liquid culture supplemented with the heme precursor 5-aminolevulinic acid to increase de novo heme synthesis (40). After induction with isopropyl ␤-D-thiogalactopyranoside, a prominent protein band of the expected 46 kDa was visible in bacterial extracts.…”
Section: Recombinant Ynl234wp Binds Noncovalently a Low Spin Form Hemmentioning
confidence: 99%
“…Studies using purified and/or recombinant enzymes have demonstrated that multiple P450s can metabolize AA and that the products depend largely on the particular P450 enzyme involved in catalysis. For example, members of the CYP2B and CYP2C subfamilies are primarily AA epoxygenases (Capdevila et al, 1990a;Rifkind et al, 1995); members of the CYP1A, CYP2E, and CYP4A subfamilies are principally -terminal hydroxylases (Capdevila et al, 1990a;Laethem et al, 1993;Nishimoto et al, 1993;Rifkind et al, 1995); and members of the CYP2J subfamily are both epoxygenases and -terminal hydroxylases (Wu et al, 1997). The epoxygenase and hydroxylase reactions are both regioselective and enantioselective, and the reaction asymmetry is P450 enzyme specific (Capdevila et al, 1990a).…”
Section: Introductionmentioning
confidence: 99%